Analysis of the survey and of the attitudes on staff, organisation and procedures : the case of local political leaders in Ho Chi Minh City - Nguyen Thi My Dai; Zimmerman, Willi; e; Sununta Siengthai; Project 300, Vietnam; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
Leaders are major drivers and carry a lot of responsibility for the reform. In the context of the administrative reform activities of the Country, Ho Chi Minh City's Justice Department had a survey on the attitudes of local political leaders about reforming civil status services. The author of this research study studied the questionnaire, used and analyzed survey data and did numerous in-depth interviews. The questionnaire, the sampling and data collection can be improved. The length of the questionnaire can be reduced; the sampling should be randomized. The content and the capabilities of the targeted respondents should be better controlled. This research then analyzes the attitudes of local political leaders about the administrative reform of the civil status services. They have a positive attitude towards the public administration reform. Regarding the management of civil status registration they survey reveals that improvements should be made. The legal provisions are to some extent overlapping and inadequate. The qualification and capacity of staff are not good enough to meet the requirements of work; the sense of responsibility should be increased. A better physical and computerized infrastructure would improve the effectiveness of the service. Civil status data should not be managed separately, dispersedly and incompatibly among agencies. Finally, the leaders welcome decentralization if it is carried out together with a comprehensive allocation of physical and human resources otherwise there is a lack of physical and human resources. Which in turn leads to inadequate civil service registration and service provision. Recommendations in relations to above mentioned 'shortcomings' are made for the Department on how to continue with the administrative reform in civil status services in Ho Chi Minh City and how to improving surveys in the public sector in Vietnam.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in International Public Management
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2007
Keywords: Public administration -- Vietnam -- Evaluation; Leadership -- Vietnam -- Attitudes